Stereoselective synthetic approaches towards (S)-duloxetine: 2000 to date. Issue 22 (15th December 2016) - Larik, Fayaz Ali; Saeed, Aamer; Channar, Pervaiz Ali; Mehfooz, Haroon
Graphical abstract: Abstract: Over the last 15 years, the synthetic community has devoted many efforts towards the enantioselective synthesis of the anti-depressant drug ( S )-duloxetine. The drug is used in the treatment of major depressive disorder, generalized anxiety disorder, urinary incontinence, neuropathic pain, chronic musculoskeletal pain, as well as fibromyalgia. This review covers the synthetic approaches during the period 2000 to date towards ( S )-duloxetine, describing the reported total synthesis strategies and chemoenzymatic methods. The key stereoselective steps involved in the syntheses are highlighted.